Leveraging unsupervised segmentation for semi-supervised renal calculi and carcinoma segmentation and classification - Faruk, Farhan; Alam, H.M. Sarwer (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.